Analisis Perbandingan Prediksi Kebangkrutan Perusahaan dengan Model Altman Z-Score, Springate, dan Grover - Herawati Khotmi (Sekolah Tinggi Ilmu Ekonomi AMM, 2020)
Business activities necessary to predict if the company is in a good state or not. In this study aims to predict bankruptcy with Model Grover, Model Althman Z-Score Model Springate and to identify the difference between Model Grover, Model Altman Z-Score Model Springate. The type of research is the descriptive, research site of PT. BPR Tresna Niaga is located on Jl. Jendral Sudirman, Tiwugalih, Praya, regency of Lombok Tengah Nusa Tenggara Barat. The data source uses secondary data. The research analysis techniques are identifying data, calculating ratio ratios, creating bankruptcy prediction categories and making conclusions. There is a difference in ratio or results Z-score by using model Grover model and Altman Z-score with model Springate in the addiction of bankruptcy. Where to model Ghover is a disdiction of PT. BPR Tresna Niaga Praya is not in the condition of bankruptcy. Unlike the model of Altman Z-Score criteria of the predictions of PT. BPR Tresna Niaga Praya in the bankruptcy condition and the same as the Model Springate predictions in the position of bankruptcy. The suggestion of this research is that the analysis results are not fully used as a result of predicting bankruptcy, by predicting there are no measures to overcome financial difficulties. It is better to have financial analysis to improve financial performance and should further researchers post the research period